Distribution of the Residual Self-Interference Power in In-Band Full-Duplex Wireless Systems - Irio, Luis (2019)
This paper derives the distribution of the residual self-interference (SI) power in an analog post-mixer canceler adopted in a wireless in-band full-duplex communication system. We focus on the amount of uncanceled SI power due to SI channel estimation errors. Closed form expressions are provided for the distribution of the residual SI power when Rician and Rayleigh fading SI channels are considered. Moreover, the distribution of the residual SI power is derived for low and high channel gain dynamics, by considering the cases when the SI channel gain is time-invariant and time-variant. While for time-invariant channels the residual SI power is exponentially distributed, for time-variant channels the exponential distribution is not a valid assumption. Instead, the distribution of the residual SI power can be approximated by a product distribution. Several Monte Carlo simulation results show the influence of the channel dynamics on the distribution of the residual SI power. Finally, the accuracy of the theoretical approach is assessed through the comparison of numerical and simulated results, which confirm its effectiveness.